Meat impaction in the distal esophagus in a healthy male - Ma Victoria V. Calubaquib (17191453) (2021)
Food bolus impaction can either be functional or mechanical. In adults, the most common cause is accidental, and the esophagus is the most common site of obstruction in the gastrointestinal tract. The patient may present with dysphagia, regurgitation, drooling, and inability to swallow liquids. We now report a case of food impaction in a healthy young adult male who presented with vomiting of liquids and the feeling of food being stuck in the throat. The fiberoptic endoscopic evaluation shows no foreign body nor pulling. However, CT scan of the neck and chest showed otherwise. Removal of the meat impacted in the distal esophagus was successfully done using endoscopy. Hence, the patient was discharged home the next day improved. As an emergency physician, we have to aim at providing optimum patient care with the early involvement of other specialties. Other Information Published in: Visual Journal of Emergency Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.visj.2021.101207